2019
DOI: 10.1177/1758155919826765
|View full text |Cite
|
Sign up to set email alerts
|

Fear and behavior of young pheasants reared with or without parent figure

Abstract: Modern game birds rearing methods use mechanical incubators to hatch eggs and artificial brooders to intensively rear birds. However, the lack of parental care can have consequences on behavior and welfare of these birds affecting also survival after their release in the wild. In this study, we compared the response of 4-week-old young pheasants (brooded by a foster mother hen and artificially brooded) to two behavioral tests (duration of tonic immobility and response to aerial predator). Tonic immobility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Lack of behavioral synchrony, as a consequence of constant, uniform heat and light may cause active birds to disturb and feather-peck resting birds (Gilani, et al 2012) which can disrupt sleeping patterns, cause injury and be stressful for the recipient. Young pheasants reared with a foster mother showed a lower stress level and a higher response to a simulated aerial predator compared to artificially reared pheasant (Santilli & Bagliacca 2019).…”
Section: Absence Of Adultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Lack of behavioral synchrony, as a consequence of constant, uniform heat and light may cause active birds to disturb and feather-peck resting birds (Gilani, et al 2012) which can disrupt sleeping patterns, cause injury and be stressful for the recipient. Young pheasants reared with a foster mother showed a lower stress level and a higher response to a simulated aerial predator compared to artificially reared pheasant (Santilli & Bagliacca 2019).…”
Section: Absence Of Adultsmentioning
confidence: 87%
“…Tonic immobility levels increased with age within a rearing treatment, suggesting either a developmental process or indicating that the individual was experiencing poorer welfare as they grew older (Nowaczewski, et al 2012). Tonic immobility was higher in chicks that were artificially reared compared to birds that were reared with foster parents suggesting that they were more fearful (Santilli & Bagliacca 2019). A final study investigated dust bathing, considered to be indicative of positive welfare in poultry (Olsson & Keeling 2005).…”
Section: Summary Of Published Work That Specifically Assesses Welfarementioning
confidence: 99%
“…However, the lack of parental care can have consequences on the behaviour and welfare of these birds and also affect their survival after their release into the wild. Santilli and Bagliacca (2019) compared the reaction of 4-week-old pheasants (brooded by a foster mother hen and artificially brooded) and found that the duration of TI differed significantly between the two groups of birds. Pheasants brooded by a foster hen showed a stronger response to aerial predator compared to artificially brooded pheasants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the chances of survival of captive-bred birds after their release into an unknown complex environment are questionable. Studies have shown that the young reared by their biological parents exhibit more effective anti-predatory behaviour including immobility than artificially brooded birds (Santilli and Bagliacca 2019). Defensive reactions increase the fitness of wild animals, their life expectancy is prolonged if they adopt effective behaviour to avoid danger, namely predators (Jones et al 1992;Dwyer 2004).…”
mentioning
confidence: 99%
“…by favoring individual traits that improve response to risk and thus survival expectancy), rather than merely on the quantity, of released individuals. This includes favoring the translocation of wild-caught individuals when possible (Sokos et al 2008), or alternatively captive-reared populations promoting parental care that reduces the level of fear of animals compared to artificial rearing (Santilli and Bagliacca 2019), anti-predator training that promotes elicitation of motor behaviors in response to predators (Gaudioso et al 2011;Sánchez-García et al 2016), minimal human contact increasing the escape and fear-related behaviors to humans (Zaccaroni et al 2007), controlled pre-exposure to pathogens (Faria et al 2010) and the maintenance of high diversity of immunogenetics improving the response to infection within the captive population (Charpentier et al 2008). S1) and variable contributions (Tables S2, S3) are available in Online resource 1 Fig.…”
Section: Management Implicationsmentioning
confidence: 99%